2013
DOI: 10.1080/17571472.2013.11493370
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the implementation of self management support in long term lung conditions

Abstract: Background Self-management improves outcomes in asthma and COPD and is strongly recommended in national and international guidelines; however implementation of the guidelines such as use of written action plans in practice is often poor. Setting A questionnaire survey was undertaken to identify the healthcare professional barriers to implementation of self-management for asthma and COPD in West London. Question Why is self-management education not being undertaken in respiratory conditions? Methods A questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…4 All met vs. Not met/Few met/None met. 5 Yes a great deal vs. Yes somewhat/No it hasn't/It made things worse.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…4 All met vs. Not met/Few met/None met. 5 Yes a great deal vs. Yes somewhat/No it hasn't/It made things worse.…”
Section: Resultsmentioning
confidence: 94%
“…A survey of doctor's attitudes to action plans in COPD revealed that the most common reason for not providing them is perceived lack of patient understanding of their illness (5). Sadeghi et al (6) also suggests that health literacy is a signifi cant barrier to self-care.…”
Section: Introductionmentioning
confidence: 98%
“…Yet, the implementation of SM in daily praxis is still limited. Barriers for the implementation are mainly related to a lack of health literacy among patients, a lack of health care professionals' belief in their patients' abilities, as well as a lack of training during medical education [2,11]. Therefore, basic, interactive, and critical health literacy is regarded as one important endpoint to improve patients' SM abilities [12].…”
Section: Current Relevance Of Self-management In Health Carementioning
confidence: 99%
“…Second, clinical practice guidelines may not be adhered to even when they clearly and explicitly recommend self-management support. For example, Roberts, Younis, Kidd, and Partridge (2013) report that in the United Kingdom, implementation of selfmanagement support for individuals with asthma and chronic obstructive pulmonary disease is inconsistent despite its inclusion in national and international practice guidelines for practicing lung specialists. Third, self-management support programs may not yield the same significant outcomes in a clinical setting as are achieved in a controlled research environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of individual clinician factors that influence the adoption of clinical innovations have been reported in the literature. These include the extent to which clinicians understand the innovation, beliefs about the value of the innovation, the level of relevant education and training, motivation to adopt the innovation, self-efficacy for performing new clinical tasks, and perceptions of how well the innovation will integrate into existing clinical protocols (Jordan & Osborne, 2007;Lake & Staiger, 2010;Moodie et al, 2011;Roberts et al, 2013). One theoretical framework that has been developed to better understand these factors, as well as others that influence behaviour, is the COM-B model.…”
Section: Introductionmentioning
confidence: 99%